(untitled) (Journal of Geography and Environmental Management, 2023)
The assessment of natural moisture availability of the natural areas of the Turkestan region of the Republic of Kazakhstan for 1941-2020 (by providing a comparative analysis of indicators for 1941-1960 and 2001-2020) was conducted based on the use of the natural moisture coefficient and hydrothermal index or "dryness index" predicated on energy resources (total of biologically active air temperatures above 10 °С, photosynthetically active radiation, evaporating capacity and water consumption of agricultural land). The results of a comparative analysis of climatic indices changes in the natural areas of the Turkestan region for 1941 to 2020 have shown that there is an increase in average annual air temperatures in all natural areas, and the annual precipitation tends downward which affects the formation of energy resources and natural water supply. The identified features of changes in the natural moisture coefficient and hydrothermal index or "dryness index" in natural area of Turkestan region, make it possible to adjust the spread of its boundaries and consider these changes in the territorial organization of agricultural nature management.